(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2024)
The academic field of memory studies in Colombia is broad and diverse. This paper seeks to interrogate the boundaries of this field, in order to explore new dialogues and perspectives. Thus, it proposes a review of the shared interests, links and areas of focus between memory studies and heritage studies in Colombia, aiming to position the connections between them and to envisage further approaches for memory studies. The review characterizes the link between heritage and memory studies, considering their relations with historical memory and cultural memory; explores other studies produced by heritage studies that are different from memory studies, but that inform and contribute to its study; and reflects on the intersections, challenges and gaps in academic studies to point out new research paths. Therefore, this paper analyses some themes in memory and heritage studies in Colombia, accounting the agendas and categories of linkage and distances. At the same time, it encourages the discussion on the future of the field from adjacent and emerging, but still little explored, thematic crossroads: heritage and development policies, tourism, and globalisation and its effects.